PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX, PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI SAHAM - Tito Albi Utama; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of Corporate Governance Perception Index (CGPI), profitability, leverage and size of the company's share value companies listed in Indonesia Stock Exchange 2007-2011. In this study, there are four independent variables, Corporate Governance Perception Index (CGPI), profitability, leverage, and firm size and one dependent variable is the value of the stock. The sampling method used in this research is purposive sampling method. The number of populations found in this study were 343 companies that meet and then purposive sampling six companies. type of regression model used in this study is multiple regression, and then to test in multiple regression studies using the Statistical Product and Service Solutions (SPSS) version 20.0 for windows using F test (ANOVA) and a test T (partial).The result of this study showed that together (Test F) all independent variables affect the value of the stock. Then the only independent variable T test Profitability, Leverage, and firm size are affeting the value of stock significantly. While corporate governance perception index variabel does not effect the value of stock.